Levels of Writing Mistakes and its treatment in the light of Modern Approaches(Students of Faculty of Arabic of IIU as Model): مستويات الأخطاء الكتابية ومعالجتها في ضوء المناهج الحديثة (طلاب وطالبات كلية اللغة العربية بالجامعة الإسلامية بإسلام آباد أنموذجا) - Ahmad, Dr. Zaheer; Ahmad, Dr. Akhlaq (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Writing skills one of the important skills while learning any language. Arabic Writing skill has multi dimensions rules should have to be followed. This analytical research is about to gather samples of writing scripts and its classification according to the types of mistakes and ratio of these mistakes among male and female students comparatively in general. In the second step of these analysis the same mistakes are compared with Pakistani and Chinese students of the faculty. It is significantly observed that Pakistani students commit less writing mistakes in comparison with Chinese students. The main reason lies that Urdu is written in Arabic script whereas Chinese script is totally different in writing script. This research will help out the teachers how to address this problem and they can guide their students to minimize these mistakes.